Heterojunction Incorporating Perovskite and Microporous Metal–Organic Framework Nanocrystals for Efficient and Stable Solar Cells - Zhou, Xuesong; Qiu, Lele; Fan, Ruiqing; Zhang, Jian; Hao, Sue; Yang, Yulin (Nano-Micro Letters, 2020)
In this paper, we present a facile approach to enhance the efficiency and stability of perovskite solar cells (PSCs) by incorporating perovskite with microporous indium-based metal–organic framework [In12O(OH)16(H2O)5(btc)6]n (In-BTC) nanocrystals and forming heterojunction light-harvesting layer. The interconnected micropores and terminal oxygen sites of In-BTC allow the preferential crystallization of perovskite inside the regular cavities, endowing the derived films with improved morphology/crystallinity and reduced grain boundaries/defects. Consequently, the In-BTC-modified PSC yields enhanced fill factor of 0.79 and power conversion efficiency (PCE) of 20.87%, surpassing the pristine device (0.76 and 19.52%, respectively). More importantly, over 80% of the original PCE is retained after 12 days of exposure to ambient environment (25 °C and relative humidity of ~ 65%) without encapsulation, while only about 35% is left to the pristine device. Highlights: 1 Microporous indium-based metal–organic framework (In-BTC) nanocrystals are synthesized under an extremely mild condition. 2 Perovskite/In-BTC heterojunction films possess improved morphology/crystallinity and reduced grain boundaries/defects. 3 In-BTC-modified perovskite solar cells exhibit significantly enhanced efficiency of 20.87% and long-term stability.